GIS Based Models in Practice: The Multimedia Assessment of Pollutant Pathways in the Environment (MAPPE) Model - Pistocchi, Alberto (GIS Based Chemical Fate Modeling, 2014)
This chapter illustrates a modeling strategy strongly based on the capabilities provided by geographic information system (GIS) through built‐in, map‐computational functions. It demonstrates a fully map‐based approach for structuring and solving the system of equations involved in multimedia, multipathway fate and transport modeling, as required in the analysis of human and ecosystem exposure to chemicals emitted in different media and subject to chemical degradation, intermedia migration, and advection. The chapter discusses a scenario study conducted by the conducted by the European Commission JRC using the multimedia assessment of pollutant pathways in the environment (MAPPE) model for lindane as well as other chemicals. The chapter discusses individual environmental compartments separately through a cascade of single‐medium calculations. These are simpler than simultaneous, coupled transport of chemicals as in a full multimedia model.